If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + 10 = k + 15 Reorder the terms: 10 + 2k = k + 15 Reorder the terms: 10 + 2k = 15 + k Solving 10 + 2k = 15 + k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. 10 + 2k + -1k = 15 + k + -1k Combine like terms: 2k + -1k = 1k 10 + 1k = 15 + k + -1k Combine like terms: k + -1k = 0 10 + 1k = 15 + 0 10 + 1k = 15 Add '-10' to each side of the equation. 10 + -10 + 1k = 15 + -10 Combine like terms: 10 + -10 = 0 0 + 1k = 15 + -10 1k = 15 + -10 Combine like terms: 15 + -10 = 5 1k = 5 Divide each side by '1'. k = 5 Simplifying k = 5
| (8/t-7)-3/t | | 15=2a-2 | | 18+6x+x^2=0 | | 5x-5y=10z | | -4/35/8/7 | | 2(4x+8)=x+7x-2 | | -7=-7x+3(x+5) | | -a+2a=4a+6-2 | | -3y=6/5 | | -4x/7=-12 | | 6x=-6x+144 | | 6x-15=5x-9 | | 5/-5 | | x-3/x= | | 6x/39 | | -5/9w=35 | | 44.95(t-25)=2511.6 | | (a+3b)+(3a-b)i=6+6i | | x×x-3/x= | | x×x-3/x=18 | | 4x^2=57 | | 10v-3=8v+9 | | 3y-3(-33)=2y+2(-33) | | 4b+4b+4b= | | 2=9z-3z+2-6z+4+z | | 3m+6m-10m=3+7-4+m | | .4(7-3x)=9+(4x-1) | | 5x+8x+11x= | | -40x+36x=30x-45 | | 2b^2+36-9=0 | | 4x-3=9x+9 | | 5x^3-3x^2-5x+3=5x^2-4x-1 |